Excitation of poloidal standing Alfvén waves through drift resonance wave‐particle interaction. Issue 16 (27th August 2013) - Dai, Lei; Takahashi, Kazue; Wygant, John R.; Chen, Liu; Bonnell, John; Cattell, Cynthia A.; Thaller, Scott; Kletzing, Craig; Smith, Charles W.; MacDowall, Robert J.; Baker, Daniel N.; Blake, J. Bernard; et al.
<x xml:space="preserve">Abstract</x> [1] Drift‐resonance wave‐particle interaction is a fundamental collisionless plasma process studied extensively in theory. Using cross‐spectral analysis of electric field, magnetic field, and ion flux data from the Van Allen Probe (Radiation Belt Storm Probes) spacecraft, we present direct evidence identifying the generation of a fundamental mode standing poloidal wave through drift‐resonance interactions in the inner magnetosphere. Intense azimuthal electric field (Eφ) oscillations as large as 10mV/m are observed, associated with radial magnetic field (Br) oscillations in the dawn‐noon sector near but south of the magnetic equator at L∼5. The observed wave period, Eφ/Br ratio and the 90° phase lag between Br and Eφ are all consistent with fundamental mode standing Poloidal waves. Phase shifts between particle fluxes and wave electric fields clearly demonstrate a drift resonance with ∼90 keV ring current ions. The estimated earthward gradient of ion phase space density provides a free energy source for wave generation through the drift‐resonance instability. A similar drift‐resonance process should occur ubiquitously in collisionless plasma systems. One specific example is the "fishbone" instability in fusion plasma devices. In addition, our observations have important implications for the long‐standing mysterious origin of Giant Pulsations.